PENERAPAN TERAPI AFIRMASI POSITIF PADA PASIEN DENGAN HARGA DIRI RENDAH DI RUMAH SAKIT JIWA Prof. DR. MUHAMMAD ILDREM MEDAN - Ginting, Iir tirana a.; Gustina, Erita; Pangaribuan, Resmi (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Low self-esteem is a feeling of shame or inferiority that is usually caused by negative judgments from oneself or others. Complications in patients with low self-esteem include social isolation, even violent behavior. One intervention that can be done for patients with low self-esteem is the application of positive affirmation therapy. Positive affirmations are utterances of sentences that can strengthen positive beliefs in a person. This research method is a descriptive study with a case study type of research. The subjects used were 2 patients with nursing problems of the application of positive affirmation therapy in patients with low self-esteem at Prof. DR. Muhammad Ildrem Mental Hospital Medan. The results of the study from the two respondents during the psychiatric nursing care with the application of positive affirmation therapy in patients with low self-esteem for 3 days with 6 meetings were obtained, both respondents were able to carry out SP 1 to SP 4 to control their lack of confidence. The conclusion of the assessment to evaluation in carrying out nursing care for patients with low self-esteem successfully controlled their lack of confidence with the application of positive affirmation therapy SP 1 to SP 4. The suggestion of this study is expected to be a reference in conducting further research on psychiatric nursing cases with low self-esteem using positive affirmation therapy.